2023
DOI: 10.1021/acscatal.2c05414
|View full text |Cite
|
Sign up to set email alerts
|

Study and Applications of Tetrasubstituted Hypervalent Selenium–Halogen Species in Catalytic Electrophilic Halogenations

Abstract: Electrophilic halogenation reactions are highly useful in various areas. N-Haloamides are commonly used as halogen sources because of high stability and commercial availability. In order to activate N-haloamides, Lewis basic chalcogens are commonly used as catalysts to site-isolate the strongly coordinating amide moieties. However, the corresponding trisubstituted chalcogenonium–halogen cationic intermediate is sensitive to moisture and nucleophiles, leading to poor compatibility in some reactions. Herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…They nevertheless required longer reaction time. [31] It is worth also mentioning that in the reactions detailed above, no degradation of the catalyst was observed, as checked by 19 F NMR spectroscopy on the crudes after reaction.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…They nevertheless required longer reaction time. [31] It is worth also mentioning that in the reactions detailed above, no degradation of the catalyst was observed, as checked by 19 F NMR spectroscopy on the crudes after reaction.…”
Section: Resultsmentioning
confidence: 84%
“…The authors have cited additional references within the Supporting Information. [34][35][36][37][38][39][40][41][42][43][44][45][46][47]…”
Section: Supporting Informationmentioning
confidence: 99%
“…[14] Recently, Yeung et al reported an efficient catalytic bromination of anisole using phenyl selenium with ortho-substituted carboxylic acid as the catalyst. [15] They found that the ChB catalysts could significantly increase the rate and yield of the reaction. Moreover, Mamane's group reported impressive ChBs with telluronium cations in the bromination of anisole, which demonstrated that NBS significantly activated by the telluronium cations catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yeung et al . reported an efficient catalytic bromination of anisole using phenyl selenium with ortho‐substituted carboxylic acid as the catalyst [15] . They found that the ChB catalysts could significantly increase the rate and yield of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly the low-valent organoselenium compounds with oxidation states of Se 0 , Se II , and Se IV , have been explored in synthetic chemistry, , materials, and in biology . The isolation of selenium in its highest oxidation state is difficult owing to inherent thermodynamic instability attributed to scandide contraction , in which period 4 elements (Ga, Ge, As, Se, Br, Kr) tend to be smaller in size and possess higher ionization energies .…”
mentioning
confidence: 99%